STRATEGI GURU DALAM MENANAMKAN KONSEP THAHARAH PADA SISWA: STUDI KASUS DI TASKA AL-FIKH ORCHARD PERDA - Novi Adelia Ramadani; Nurul Zahriani JF (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Education is a deliberate attempt to enhance pupils' potential, particularly their spiritual and noble qualities. Thaharah (pembersihan) is a fundamental principle in Islamic education that serves as a foundation for good deeds. This study investigates the strategy used by teachers at Taska Al-Fikh Orchard Perda to teach the concept of thaharah to children aged 1-4. Data were collected using qualitative research methods such as observation, questionnaires, and documentation. The theory states that the teacher use a long-term learning strategy that incorporates demonstration, practice, and game methods. This comprehensive approach transforms abstract shariah law into concrete human needs like as eating, sleeping, and performing rituals. Students respond with high enthusiasm, resulting in significant changes in behavior in terms of discipline and hygiene. The primary factor is a strong bond between school and parents, while the secondary factor is a child's deteriorating cognitive memory and occasional enggan. This study found that consistent instruction and interactive methods are critical in developing the spiritual character and discipline of children. By including thaharah as a component of daily routines, educational institutions can effectively balance theoretical knowledge with practical application.